Experimental study on the thermal management performance of phase change material module for the large format prismatic lithium-ion battery. (1st January 2022) - Zhou, Zhizuan; Wang, Dong; Peng, Yang; Li, Maoyu; Wang, Boxuan; Cao, Bei; Yang, Lizhong
Abstract: Phase change material (PCM) technology is an interesting method for battery thermal management, while the cooling behavior and cooling efficiency of PCM on prismatic lithium-ion batteries are unclear. In this work, a series of experiments are conducted to systematically investigate the cooling efficiency of PCM and the several detailed factors on the thermal management performance, such as the structure, phase change temperature and thickness of PCM. The results show that the PCM structure (sides of the battery surround by PCM) has an excellent heat dissipation efficiency at high discharge rate of 2C. Decreasing the phase change temperature is beneficial to enhance the cooling performance. Moreover, increasing the thickness of PCM enhances the cool performance, but the heat dissipation efficiency will decrease once the thickness exceeds the value of 25 mm, hence the selection of the PCM thickness is variable based on the heat dissipation capability and cooling efficiency. Furthermore, by investigating the cooling behavior of PCM during the cycle test, it is found that the PCM structure with 25 mm thickness can keep the maximum temperature of the battery under 55 °C in dynamic cycling. This work can provide experimental references for the thermal management system of prismatic batteries. Highlights: The thermal performance of large format lithium-ion battery during charge and discharge stages was experimentally studied. Quantifying the heat dissipation capacity and heat dissipation efficiency of PCM in the battery thermal management. The effects of phase change temperature and thickness of PCM on the thermal management system were analyzed. The PCM module with 25 mm thickness has an excellent cooling performance in dynamic cycling.